Enhancing Engineering Technology Production according to the philosophy of (Jidoka) Japanese - An analytical study of a sample of managers and heads of departments in the Electricity Department of Babylon Governorate - Fatima Hussein Kazem Al-Bakri (Peerian Journals Publishing, 2023)
The research focused on studying the nature of the relationship and its impact between production engineering techniques and the Japanese philosophy of JIDOKA. The research problem revolved around an important question: How can production engineering techniques be enhanced through the Japanese philosophy of JIDOKA in the selected sample? To address this, managers and department heads in the Electricity Department of Babil Province were purposefully chosen as the research sample. Various statistical methods and software, including SPSS and Excel, were employed. The research yielded several conclusions, the most significant of which was the significant impact of positive reinforcement of production engineering techniques on improving and evaluating productivity through the structures, machines, equipment, tools, and manufacturing processes that form the foundation of quality in the field. One of the key recommendations endorsed by the research was the necessity of optimal investment in production engineering techniques and directing them towards fulfilling the hidden societal requirements while increasing awareness of the agile-oriented Japanese philosophy of JIDOKA in the research community.
Keywords: production technology engineering; philosophy; JIDOKA